Active dynamic windows for buildings: A review. (April 2018) - Casini, Marco
Abstract: The objective of answering the growing demand of environmental comfort and the urgent need to improve energy efficiency of new and existing buildings, are determining an in-depth review of the features and requirements of the building transparent closures towards technological solutions that can guarantee along with a maximum thermal insulation, the possibility to regulate the incoming solar radiation or generate electrical energy. Thanks to the huge progress in the field of materials science, a new class of highly innovative glazing systems is entering the market mostly by taking advantage of key enabling technologies such as nanomaterials or smart materials. Among these new technologies, active dynamic glazing, by modulating the amount of entering near infrared radiation and visible light, allows significant energy savings, as well as ensuring greater thermal and visual comfort for occupants. The article offers a thorough review of active dynamic glazing technologies on the market or in development, such as electrochromics, gasochromics, and further emerging technologies, including nanocrystal in-glass composites, electrokinetic pixels, elastomer-deformation tunable window, and liquid infill tunable window, comparing them in terms of operation, performances and building application potential, and providing relevant data to aid in understanding impacts on energy-efficiency and comfort. Highlights: Highly innovative glazing for the building envelope is discussed. Active dynamic glazing technologies available or in development are thoroughly reviewed. Performance and benefits/drawbacks of different smart windows technologies are compared. Needs for improvement and future trends of active dynamic glazing are considered.